Nonalcoholic fatty liver disease and sarcopenia in a Western population (NHANES III): The importance of sarcopenia definition. Issue 1 (February 2019) - Peng, Tao-Chun; Wu, Li-Wei; Chen, Wei-Liang; Liaw, Fang-Yih; Chang, Yaw-Wen; Kao, Tung-Wei
Summary: Background: Recent epidemiological studies have shown that sarcopenia is associated with non-alcoholic fatty liver disease (NAFLD) and advanced fibrosis in an Asian population. We investigated whether NAFLD is associated with a higher risk of sarcopenia using a different definition in elderly patients. Methods: A population-based cross-sectional survey of US patients was conducted, involving 2551 participants aged 60–75 years. NAFLD was measured by ultrasound. Sarcopenia was defined by both a low muscle mass and poor muscle function. In addition, the skeletal muscle index (SMI) was calculated as the absolute muscle mass (kilograms) divided by height 2 (meters) or total body mass (kilograms). A multivariable logistic regression was conducted to estimate the relationship between sarcopenia and NAFLD in the elderly. Results: After adjusting for age, sex, and race/ethnicity, severe hepatic steatosis was associated with a decreased risk of sarcopenia as defined by the height-adjusted SMI (odds ratio (OR) 0.63; 95% confidence interval (CI) 0.46–0.87). In contrast, severe hepatic steatosis was associated with an increased risk of sarcopenia as defined by the weight-adjusted SMI (OR 1.73; 95% CI 1.31–2.28). These significant associations remained after further adjustments for other potential confounding variables. Conclusions: NAFLD is associated with a lower risk of sarcopenia when using the height-adjusted SMI. In contrast, it showed the opposite result when using the weight-adjusted SMI. The definition of sarcopenia may be an important factor when examining its relationship with NAFLD.